Studies on the role of alpha 7 nicotinic acetylcholine receptors in K562 cell proliferation and signaling - AYDIN OMAY, BANU; CABADAK, HÜLYA (SPRINGER, 2021)
The results we obtained from this study gave information about the determination of alpha 7 nicotinic acetylcholine receptor (alpha 7-nACh) expression in human erythroleukemia cells, as well as whether it has a role in calcium release and cell proliferation in the presence of nicotinic agonist, antagonists. Determining the roles of alpha 7 nicotinic receptors in erythroleukemia cells will also contribute to leukemia-related signal transduction studies. This study is primarily to determine the role of nicotinic agonists and antagonists in cell proliferation, alpha 7 nicotinic acetylcholine receptor expression, and calcium release. The aim of this study, which is a continuation and an important part of our previous studies on the cholinergic system, has contributed to the literature on the human erythroleukemia cell signaling mechanism. Cell viability was evaluated by the trypan blue exclusion test and Bromodeoxyuridine/5-Bromo-2 '-deoxyuridine (BrdU) labeling. Acetylcholine, nicotinic alpha 7 receptor antagonist methyllycaconitine citrate, and cholinergic antagonist atropine were used to determine the role of alpha 7-nACh in K562 cell proliferation. In our experiments, the fluorescence spectrophotometer was used in Ca2+ measurements. The expression of nicotinic alpha 7 receptor was evaluated by western blot. The stimulating effect of acetylcholine in K562 cell proliferation was reversed by both the alpha 7 nicotinic antagonist methyllycaconitine citrate and the cholinergic antagonist, atropine. Methyllycaconitine citrate inhibited K562 cell proliferation partially explained the roles of nicotinic receptors in signal transduction. While ACh caused an increase in intracellular Ca2+, methyllycaconitine citrate decreased intracellular Ca2+ level in K562 cell. The effects of nicotinic agonists and/or antagonists on erythroleukemic cells on proliferation, calcium level contributed to the interaction of nicotinic receptors with different signaling pathways. Proliferation mechanisms in erythroleukemic cells are under the control of the alpha 7 nicotinic acetylcholine receptor via calcium influx and different signalling pathway.
Keywords: Cholinergic system; Nicotinic receptor; Acethylcholine; Antagonist; Agonist; K562 cells; CANCER CELLS; ANGIOGENESIS; STIMULATION; ACTIVATION; PLATELETS; APOPTOSIS; AGONIST; SYSTEM; GROWTH; ACTS